Fragmented But Not Fractured: Implications For the Resilience Profile of Incarcerated Youth in Indonesia - Maxey, William; Setiawati, Sri; Setiawan, Hari Harjanto; Febriamansyah, Rudi (Universitas Andalas, 2025)
As part of a larger action research cycle, this study reflected on the resilience of incarcerated male youths (N=74, aged 14-20) in West Sumatra, Indonesia. Using the “CYRM-R Plus Spirituality and Religiosity” measure, four subscales—Interpersonal, Caregiver, Spirituality, and Religiosity—were assessed using quantitative comparative analysis to create a resilience profile. The population was compared to a national normative sample of Indonesian males (N=3,496) within a similar age range. While Interpersonal and Caregiver support scores were comparable to the normative data, the item-level analysis revealed strong caregiver practical support but emotional distance and limited peer connection within the incarcerated youth, despite high behavioral adaptability. In contrast, Spirituality and Religiosity emerged as significant strengths of the population, with notably higher scores and large effect sizes when compared to the national sample, particularly in religious practice and beliefs about divine purpose. These findings demonstrate remarkable inner resources within incarcerated youth, which underscore the value of resilience-informed, spiritually sensitive, and family-engaged transition planning. Incorporating youth voice, culturally sensitive programs, and holistic approaches to reentry programs would strengthen the existing resilience of incarcerated youth.